Forecasting zonation of oil-gas prospects in the sedimentary basins of the Northeast Vietnam continental shelf based on gravity and borehole data - Tran, Tuan Duong; Tran, Tuan Dung; Tran, Trong Lap; Tran, Hoang Tam; Pham Le, Hoang Linh; Nguyen, Van Thanh (Vietnam Journal of Marine Science and Technology, 2022)
This study used the 2D and 3D normalized total gradient (NTG) method of gravity anomalies to detect the gravity anomalies caused by oil-gas reservoirs. The NTG of gravity anomalies can be associated with known oil-gas reservoirs, and most of them seem to be a good coincidence with the reservoirs. The closed minima of the NTG of gravity anomalies indicate the existence and locations of the density deficient anomalies closely related to the possible oil-gas reservoirs. The reliability of the NTG method depends mainly on the Fourier-developed coefficient N. Here, N is optimally selected by the borehole data. The 2D, 3D normalized total gradient method is applied in the sedimentary basins of the Northeast Vietnam continental shelf. Borehole data confirm the results of the method.